Nazi propaganda for the Arab world - Herf, Jeffrey 1947- (Yale University Press, 2009)
Jeffrey Herf, a leading scholar in the field, offers the most extensive examination to date of Nazi propaganda activities targeting Arabs and Muslims in the Middle East during World War II and the Holocaust. He draws extensively on previously unused and little-known archival resources, including the shocking transcriptions of the ́ʺAxis Broadcasts in Arabić radio programs, which convey a strongly anti-Semitic message